THE PROBLEM OF ADEQUACY IN THE THEORY OF SIMULTANEOUS TRANSLATION (Web of Teachers: Inderscience Research, 2026)
The present article examines the problem of adequacy in the theory of simultaneous translation. It explores the conceptual differences between adequacy and equivalence, analyzes linguistic and extralinguistic challenges faced by interpreters, and discusses strategies used to achieve adequate translation under time constraints. The study highlights the role of cognitive processes, contextual adaptation, and pragmatic considerations in ensuring communicative effectiveness in simultaneous interpreting.